Characteristic Earthquake Magnitude Frequency Distributions on Faults Calculated From Consensus Data in California. Issue 12 (15th December 2018) - Parsons, Tom; Geist, Eric L.; Console, Rodolfo; Carluccio, Roberto
Abstract: An estimate of the expected earthquake rate at all possible magnitudes is needed for seismic hazard forecasts. Regional earthquake magnitude frequency distributions obey a negative exponential law (Gutenberg‐Richter), but it is unclear if individual faults do. We add three new methods to calculate long‐term California earthquake rupture rates to the existing Uniform California Earthquake Rupture Forecast version 3 efforts to assess method and parameter dependence on magnitude frequency results for individual faults. All solutions show strongly characteristic magnitude‐frequency distributions on the San Andreas and other faults, with higher rates of large earthquakes than would be expected from a Gutenberg‐Richter distribution. This is a necessary outcome that results from fitting high fault slip rates under the overall statewide earthquake rate budget. We find that input data choices can affect the nucleation magnitude‐frequency distribution shape for the San Andreas Fault; solutions are closer to a Gutenberg‐Richter distribution if the maximum magnitude allowed for earthquakes that occur away from mapped faults (background events) is raised above the consensus threshold of M  = 7.6, if the moment rate for background events is reduced, or if the overall maximum magnitude is reduced from M  = 8.5. We also find that participation magnitude‐frequency distribution shapes can be strongly affected by slip rate discontinuities along faults that may be artifacts related to segment boundaries. Plain Language Summary: While we know that in large regions, earthquakes obey an exponential distribution (Gutenberg‐Richter), it has been unclear whether individual faults do as well, or whether they follow a characteristic distribution. We find using three new methods to solve for the earthquake rate on California faults that all solutions are consistent with characteristic distributions, with greater numbers of large earthquakes relative to small than expected from a Gutenberg‐Richter trend. Key Points: Earthquake magnitude‐frequency on faults is suggested to be distributed in an exponential law (Gurenberg‐Richter) or characteristic We use consensus data from California to solve for the magnitude‐frequency distribution on all known faults in the state We find that individual faults have characteristic magnitude distributions